2018
DOI: 10.1002/ente.201800011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of MoS2 and Graphene Composites as the Anode Materials for Li–Ion Batteries

Abstract: The MoS2 and N‐doped graphene (MoS2/NG) composites are fabricated by an ethylenediamine‐assisted hydrothermal method for the anode materials of lithium‐ion batteries. The effects of hydrothermal systems with different amount ethylenediamine on the morphology of the MoS2 in the prepared composites are investigated. The microstructure and morphology of the as‐obtained composites are characterized by SEM, TEM and XRD methods. The analytical result reveals that the ultrathin few‐layered MoS2 nanosheets are tightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Lithium‐ion batteries (LIBs) have been widely used for portable electronic devices, due to its advantages of high energy density, no memory effects, and long‐term cycling stability . In commercial LIBs, graphite is commonly used as the anode active material because of its low and flat working potential, cost‐effectiveness, and long cycle life.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium‐ion batteries (LIBs) have been widely used for portable electronic devices, due to its advantages of high energy density, no memory effects, and long‐term cycling stability . In commercial LIBs, graphite is commonly used as the anode active material because of its low and flat working potential, cost‐effectiveness, and long cycle life.…”
Section: Introductionmentioning
confidence: 99%
“…The other way of improving the electrochemical performance of MoS 2 is by introducing carbon material, which can improve the overall conductivity and alleviate the volume expansion effect. Wang [21] reported that the MoS 2 and N-doped graphene (MoS 2 / NG) composites fabricated via an ethylenediamine-assisted…”
Section: Introductionmentioning
confidence: 99%
“…The other way of improving the electrochemical performance of MoS 2 is by introducing carbon material, which can improve the overall conductivity and alleviate the volume expansion effect. Wang [ 21 ] reported that the MoS 2 and N‐doped graphene (MoS 2 /NG) composites fabricated via an ethylenediamine‐assisted hydrothermal method exhibits superior cycling performance by adjusting the concentration of ethylenediamine. Hierarchically porous MoS 2 /C composite aerogel studied by Zhang [ 22 ] exhibited a better rate capability with a specific capacity of 653.2 and 334.5 mAh g −1 at 0.1 and 5.0 A g −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Driven by the demand of new energy vehicles and stationary storage systems, high‐performance batteries have attracted increasing attention . Lithium ion batteries (LIBs) have become competitive candidate of most electric vehicle companies, including Tesla, Toyota, BYD, etc ., due to their high energy density, high working voltage, long lifespan and environmental geniality ,. However, current commercial graphite‐based anode materials (372 mAh g −1 ) are far from satisfying the actual demand for high energy density.…”
Section: Introductionmentioning
confidence: 99%